Ultrasound-Guided Percutaneous Irrigation of Calcific Tendinopathy - Messina, Carmelo; Sconfienza, Luca Maria (Seminars in Musculoskeletal Radiology, 2016)
Rotator cuff calcific tendinopathy (RCCT) is a common disease that may cause highly disabling shoulder pain. No treatment is required for asymptomatic calcifications; mild symptoms may be treated conservatively. Among several therapeutic options, ultrasound-guided percutaneous irrigation of calcific tendinopathy (US-PICT) is currently accepted as the first-line safe and effective treatment for RCCT, with significant pain improvement and a very low rate of minor complications. Different approaches have been reported to dissolve calcified deposits, all including the use of a fluid (local anesthetic or saline solution) and the use of one or two needles to inject and retrieve the fluid/dissolved calcium. This review describes both one-needle and two-needle US-PICT techniques, providing technical and practical information that can improve daily clinical practice.
Keywords: shoulder; calcific tendinopathy; rotator cuff; ultrasound-guided procedures; ultrasound-guided percutaneous irrigation